Scrolling Minds: TikTok’s Impact on Critical Thinking in the Digital Age - Jumiyati (Winaya Inspirasi Nusantara Foundation, 2022)
The swift ascendance of TikTok as a preeminent short-form video platform has elicited increasing apprehension among educators and psychologists over its possible effects on users' cognitive abilities, especially critical thinking. The platform provides innovative methods of interaction and communication; nevertheless, its rapid, algorithm-based material distribution may hinder introspective and critical thinking. This study intends to rigorously analyse the correlation between TikTok usage and critical thinking by integrating results from 30 peer-reviewed studies published from 2018 to 2025. The study utilised a critical review methodology to carefully analyse empirical and theoretical literature from several fields, including psychology, education, and media studies. Articles were chosen based on relevance, methodological rigour, and conceptual clarity, and were thematically analysed to discern trends, conflicts, and gaps in the current research. The analysis identified four principal themes: (1) cognitive overload and attention fragmentation linked to extended TikTok usage, (2) algorithmic reinforcement of cognitive biases, (3) constrained yet intriguing teaching opportunities, and (4) notable methodological inconsistencies among studies. Although the majority of research indicates a negative link between TikTok usage and critical thinking, a few studies emphasise the platform's potential when utilised deliberately for educational objectives. These findings emphasise the necessity for more stringent, theory-based research and advocate for educational programs that enhance critical media literacy. This study enhances the existing literature on the cognitive effects of digital media and establishes a basis for future research on the changing interplay between technology and cognition.